Western Serengeti people shall not die: the relationship between Serengeti National Park and rural household economies in Tanzania - Knapp, Eli J., author; Galvin, Kathleen, advisor (Colorado State University. Libraries, 2009)
This research examined the relationship between Serengeti National Park and rural household economies living near (within 18 kilometers) its western borders in Tanzania. The study was based upon semi-structured household interviews with a general sample (N = 722), acknowledged poachers (N = 104), households with park-related employment (N = 50) and key informants (N = 15) in three two administrative regions and three districts. Interviews generated information about four primary social-ecological interactions which included crop destruction by wildlife, illegal hunting, park-related employment, and wildlife depredation on livestock. A cost-benefit analysis revealed that the average household generates a net profit of USD $13 from these interactions. Despite this, 84 percent of households were found to be food insecure for maize, the region's primary food crop. Moreover, 78 percent of households were found to be significantly over-budget over the preceding 12 months. These findings suggests that most households next to Serengeti National Park are generally impoverished and are lacking adaptive capacity to deal with severe environmental or socio-ecological changes. The first component of the research provided the context for western Serengeti. Significant findings included the importance of secondary education for increasing income to household economy and showed the level of dependence that households have on local natural resources. Households draw more heavily (often illegally) from the National Park with the advent of severe crop failures which were found to occur with a ten year periodicity. The second component revealed that neither crop damage nor wildlife depredation on livestock is distributed evenly. Rather, they are heavily localized with few effects on some households and severe effects on others. Although the effects of wildlife on crops and livestock generally decreased with distance from the Park, losses were particularly large for households within three kilometers of a boundary. The third component examined illegal bushmeat hunting and sales. Findings from respondents and extensive court documents suggested that fines and imprisonment had little effect on curbing illegal hunting behavior. The fourth component consisted of a synthesis of the cost-benefit analysis with a focus on food security and its effects on adaptive capacity. Implications of these findings are made for the resilience of the coupled socio-ecological system in western Serengeti.
Keywords: crop destruction; human-wildlife conflicts; poaching; rural households; Serengeti National Park; Tanzania; cultural anthropology; histology